State-led Forest Development and Social Protest in East Nusa Tenggara Province - Dhosa, Didimus Dedi (Forest and Society, 2021)
This research examines models of social resistances in response to top-down forest governance in the provincial government of East Nusa Tenggara Province,  Indonesia. The researcher demonstrates the models of (1) forest management and (2) people’s resistance against the regional government.The author found three fundamental problems through the perspectives of the right to the governing authority of the state and social resistance. First, the provincial government monopolise forest management since 1982 for cattle breeding.  Instead of offering prosperity to the people, this forest management model excludes the people from the forest and cattle resources. Second, when the signed contract ended, the local residents refused to extend forest management concessions to the provincial government. Third, the refusal by the residents was carried out through various forms of social movements and cultural politics. However, the provincial government mobilised the police, the civil service police, and the armed forces to intimidate the resistant communities.